PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN ANTUSIAS DALAM PROSES PEMBELAJARAN BAHASA INDONESIA SISWA KELAS IV SD INPRES 3 BIROBULI - Ni Putu Novi Damayanti; Nashrullah; Arni (STKIP Subang, 2024)
This study aims to increase the enthusiasm for learning Indonesian language subjects through the application of interactive media for fourth-grade students at SD Inpres 3 Birobuli. This study uses the Classroom Action Research (CAR) method, which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 20 fourth-grade students. Data were collected through observation, interviews and documentation, then analyzed descriptively to see the increase in student enthusiasm for learning. The indicator of success in this study is the achievement of 80% of students who have high enthusiasm for learning. The results showed a significant increase in each indicator of student enthusiasm for learning after the application of interactive media. The average percentage of student enthusiasm for learning increased from 55.5% in the pre-cycle, to 76.3% in cycle I, and reached 87% in cycle II. These findings indicate that interactive media can increase student enthusiasm for learning, by making the learning process more interesting and motivating. The application of interactive media in learning is recommended to continue to be developed and adjusted to student needs in order to achieve optimal learning outcomes.